TERAPI MUSIK MENURUT AL-FARABI PADA MASA DINASTI ABBASIYAH - Ro Hani, Suryo Ediyono (Arabic Literature Department, 2019)
This study was intended to describe the functions and instruments of music during the Abbasid Dynasty and to describe music therapy according to Al-Farabi. The research method used is the descriptive qualitative method, where the data were technically collected using the library technique, then the data were analyzed based on the formulated problem, following after it describes the analysis results in the form of a written report. The data sources are the reference books related to Al-Farabi. The data of this study used Mūsīq Al-Kabīr, books, theses, journals related to the research. Based on this research, it can be concluded that the art of music began to develop rapidly during the Abbasid caliphate, and music can be used as a therapy for the soul, spiritual, and psychosomatic.